2018
DOI: 10.1002/anie.201804059
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Silver Cluster Isomerism and Mixed Linkers to Modulate the Photoluminescence of Cluster‐Assembled Materials

Abstract: Silver chalcogenolate cluster assembled materials (SCAMs) are a category of promising light-emitting materials the luminescence of which can be modulated by variation of their building blocks (cluster nodes and organic linkers). The transformation of a singly emissive [Ag (SBu ) (CF COO) (bpy) ] (Ag bpy, bpy=4,4'-bipyridine) into a dual-emissive [(Ag (SBu ) (CF COO) (bpy) )] (Ag bpy-2) via cluster-node isomerization, the critical importance of which was highlighted in dictating the photoluminescence properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 170 publications
(110 citation statements)
references
References 98 publications
6
98
0
Order By: Relevance
“…For SD/Ag50 , its maximum emission peak red-shifts from 674 nm at 93 K to 686 nm at 233 K with gradually decayed emission intensity, after which no obvious emissions can be detected above 253 K. These NIR emissions at cryogenic temperature can be similarly attributed to the ligand-to-metal charge transfer (LMCT, charge transfer from S 3p to Ag 5 s) perturbed by Ag···Ag interaction 41 , 42 . The temperature-dependent emissions should be in the connection with the variations of molecule rigidity and argentophilicity under different temperatures 43 , 44 . The emission lifetimes of both SD/Ag44 and SD/Ag50 at 93 K fall in the microsecond scale (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For SD/Ag50 , its maximum emission peak red-shifts from 674 nm at 93 K to 686 nm at 233 K with gradually decayed emission intensity, after which no obvious emissions can be detected above 253 K. These NIR emissions at cryogenic temperature can be similarly attributed to the ligand-to-metal charge transfer (LMCT, charge transfer from S 3p to Ag 5 s) perturbed by Ag···Ag interaction 41 , 42 . The temperature-dependent emissions should be in the connection with the variations of molecule rigidity and argentophilicity under different temperatures 43 , 44 . The emission lifetimes of both SD/Ag44 and SD/Ag50 at 93 K fall in the microsecond scale (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The silver chalcogenolate clusters act as the pillars of the layered framework and the enlarged space caused by layer separation was filled with solvent molecules to support the AA stacking structure, thus various physicochemical reactions may take place owing to the surface affinity to guest molecules. The root cause why CH 3 CN could induce the re‐arrangement to form the resulting rectangle‐like structure in Ag 10 bpa may be the interactions through the synergistic effects of hydrogen bonds, dispersion, and polarity between solvent molecules with a high solubility parameter and the groups of ‐ t Bu of thiolate, ‐CF 3 , and linker bpa …”
Section: Resultsmentioning
confidence: 99%
“…However, the research about this aspect is still limited. Structural transformations triggered by solvent, including for SCAMs, are interesting and useful,, which could produce novel structures and have potential applications in molecular switches, sensors, data storage, and display devices . Relatively subtle electronic modifications to the linker can induce differing structures, although there are as yet no reported examples of their influences in single‐crystal to single‐crystal structural transformations.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Mechanism research showed that there is typical matrix coordination induced emission (MCIE) effect in Ag 12 CPPP . Furthermore, this is the first example of a SCAM constructed by using nitrile as the connecting ligand . Our approach using a rigid tetradentate ligand containing cyanophenyl and pyridyl groups paves a new way to construct porous SCAMs with intense luminescence.…”
Section: Introductionmentioning
confidence: 99%